Valorization of a mining effluent by selective recovery of Zn using solvent extraction - Avila M.; Perez G.; Valiente M. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
Zn is a typical metal component of acidic mining waters. Its selective recovery is a goal to valorize such effluents and also to minimize the cost for the mandatory treatment of such effluents. To this purpose, a solvent extraction process was developed successfully in our laboratories after comparing the results of applying different organophosphorous acids such as di-2(-ethylhexyl)-phosphoric acid (D2EHPA) and bis- (2,4,4-trimethylpentyl)-phosphinic acid (CYANEX 272 and IONQUEST 290) to a specific acidic mine effluent of South Spain (Aznalcollar Mine). Results showed that kinetics is faster with CYANEX 272 (CY) and IONQUEST 290 (IQ) than with DEHPA, reaching a 95 percent of the Zn recovery at less than 5 minutes for CY and IQ and 10 min for DEHPA. Regarding the selectivity, DEHPA extracts more efficiently Al and Ca than Zn. Ca is re-extracted from the organic phase to the stripping phase, providing an effluent almost saturated with gypsum, that will interfere in the EW process. In addition, Al is not re-extracted from the organic phase causing poisoning of DEHPA and avoiding their future reutilizations. On the other hand, neither IQ nor CY indicates Al, Cu, Mn or Ca enrichment in the stripping solution thus there is no need for scrubbing the organic phase. IQ recovery of Zn is 5-10 percent higher than for CY. Taking into account all these results, the best solvent considered for the extraction of Zn was IONQUEST 290.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)